2007
DOI: 10.1007/s10577-007-1119-0
|View full text |Cite
|
Sign up to set email alerts
|

The region homologous to the X-chromosome inactivation centre has been disrupted in marsupial and monotreme mammals

Abstract: Marsupial, as well as eutherian, mammals are subject to X chromosome inactivation in the somatic cells of females, although the phenotype and the molecular mechanism differ in important respects. Monotreme mammals appear to subscribe at least to a form of dosage compensation of X-borne genes. An important question is whether inactivation in these non-eutherian mammals involves co-ordination by a control locus homologous to the XIST gene and neighbouring genes, which play a key regulatory role in human and mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 61 publications
6
73
0
3
Order By: Relevance
“…This absence of enrichment in repressive marks is consistent with the absence of the XIST gene from the marsupial genome (Duret et al 2006;Hore et al 2007). Indeed, recruitment of H3K27me3, and probably also of H3K9me2, depends on XIST RNA localization in eutherians (Kohlmaier et al 2004).…”
Section: Status Of Inactive Marks On the Marsupial Inactive X Chromosomesupporting
confidence: 76%
See 1 more Smart Citation
“…This absence of enrichment in repressive marks is consistent with the absence of the XIST gene from the marsupial genome (Duret et al 2006;Hore et al 2007). Indeed, recruitment of H3K27me3, and probably also of H3K9me2, depends on XIST RNA localization in eutherians (Kohlmaier et al 2004).…”
Section: Status Of Inactive Marks On the Marsupial Inactive X Chromosomesupporting
confidence: 76%
“…Physical mapping and bioinformatic analyses revealed that the region homologous to the X inactivation centre is disrupted by independent rearrangements in marsupials and monotremes (Hore et al 2007;Shevchenko et al 2007), and it was suggested that XIST evolved from a protein coding gene (Lnx3) in this region, whose loss of function coincided with pseudogenization of flanking genes (Duret et al 2006). These findings challenge a pivotal role in X inactivation for XIST and raise many fundamental questions about the mechanism and evolution of this important epigenetic system.…”
mentioning
confidence: 99%
“…found no match to the highly conserved 150-bp region overlapping the critical exon 4 of XIST; this region is so strongly conserved in the Eutheria that it should be readily detectable if present 40 .) Analysis of synteny in the regions surrounding the eutherian XIC also revealed that it has been disrupted by large-scale rearrangements (Fig.…”
Section: Chromosome Inactivationmentioning
confidence: 96%
“…Expanded views, at a resolution of 50 kb, of the XAR-XCR fusion and the XIC are shown on the bottom left and right, respectively. In the XIC region, the closest contig on the distal flank (*) was not anchored in the monDom5 assembly (see Methods), but has been subsequently mapped near UPRT (opossum X chromosome ,55 Mb) by FISH 40 .…”
Section: Chromosome Inactivationmentioning
confidence: 99%
See 1 more Smart Citation